I want a dog for Christmas, Charlie Brown [videorecording (DVD)] - Mendelson, Lee; Melendez, Bill; Leichliter, Larry; Guaraldi, Vince; Benoit, David; Schulz, Charles M. (Charles Monroe), 1922-2000 (Peanuts classic., 2009)
Linus and Lucy's baby brother, Rerun, believes he'll be the happiest little boy in the world if he receives one very special Christmas gift - his own dog. Unfortunately, his mom won't get him one, and he doesn't have the ten million dollars Charlie Brown says it will cost to buy Snoopy. Rerun figures there must be a way, and when he learns that Snoopy's brother, Spike, is coming to visit, he decides that he'll adopt him.